Go Back Home? The Experience of Argentine Exiles Return (Andamios, Revista de Investigación Social, 2013)
This article seeks to investigate about return experience of argentine politicians migrants that returned home in early ‘80 from his exile in Mexico, driven by the democratic transition. From cultural sociology, we wonder about the meaning of the return after exile and about the interaction of these actors with the political and social memory of that time. The political comeback is understood as a new immigrant experience that means a sudden break with the horizons of previous expectations of these actors. In the confusion produced by a country that has changed, a new framework of experience is founded and makes the returnees rebuild the meanings of everyday life.
Keywords: Cultural sociology; experience; exile; returns